Portrait of the ideal employee - Shmatko, K. S. (ТДАТУ, 2019)
Looking at the development of electronic tools, we can say that they already allow different socio-types to make the choice of the most convenient means for themselves and if not completely, then at least partially get away from traditional paper planning, while winning in speed, capabilities and convenience.
Keywords: convenient personal time management; to-do list; Internet